Of Military Patriotic Education Methodological Theoretical Basis - Polatov Bahadir; Gʻofurov Shahboz Shavkatjon o’g’li; Mo’minov Azizbek Tojali o’g’li; Yusupov Shahzodbek bahodirjon o’g’li (Genius Journals, 2022)
The Republic of Uzbekistan undertakes the tasks of ensuring the safety, peace and stability of citizens while conducting peace policy. According to the Charter of the United Nations, it implements the inviolable right to defense, and provides military and defense power of the state at the level of intellectual sufficiency.
Keywords: Military And Defense Power; Military education; sufficiency; inviolable